2020 Development effectiveness review. (Development effectiveness review., 2020)
The operational priorities of Strategy 2030 focus on pressing development challenges in Asia and the Pacific. ADB efforts to respond to these challenges in line with operational priorities are highlighted in this publication. It is the 14th in the series of annual reports that tracks development progress in Asia and the Pacific, assesses ADB development effectiveness, and identifies areas where the institution's performance needs to be strengthened.